2017
DOI: 10.18632/oncotarget.16890
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption and the risk of ovarian cancer: A meta-analysis of epidemiological studies

Abstract: A large number of epidemiological studies have provided conflicting results about the relationship between tea consumption and ovarian cancer. This study aimed to clarify the association between tea consumption and ovarian cancer. A literature search of the MEDICINE, Scopus, PubMed, and Web of Science databases was performed in April 2016. A total of 18 (11 case-control and 7 cohort) studies, representing data for 701,857 female subjects including 8,683 ovarian cancer cases, were included in the meta-analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…A pioneering study in the mid-1990s summarized the available epidemiologic information and found that tea consumption is likely to have beneficial effects on reducing the cancer risk in some people [1]. Recently, a meta-analysis found an inverse association between tea consumption and cancer risk [4,58,59,60,61]. However, some evidence does not support the hypothesis that tea can reduce the risk of cancer [62,63].…”
Section: Tea Resists Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…A pioneering study in the mid-1990s summarized the available epidemiologic information and found that tea consumption is likely to have beneficial effects on reducing the cancer risk in some people [1]. Recently, a meta-analysis found an inverse association between tea consumption and cancer risk [4,58,59,60,61]. However, some evidence does not support the hypothesis that tea can reduce the risk of cancer [62,63].…”
Section: Tea Resists Carcinogenesismentioning
confidence: 99%
“…The functional composition of tea consists of tea polyphenols, tea polysaccharides, L -theanine, tea pigments, caffeine, and tea saponin, some of which are secondary metabolites generated by tea. These active chemicals contribute to the many important properties of tea, such as anti-cancer, anti-aging, anti-microbial, anti-inflammatory, hypoglycemic, and hypotensive activities, along with maintaining health and controlling diseases in human [3,4,5,6,7]. As a major compound, polyphenols are rich in tea (about 30%) and possess anti- or pro-oxidative properties that have been studied widely for more than 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…Two investigators independently assessed the validity of the studies using the Jadad Score [10]. The Jadad score assesses randomisation, blinding, and attrition to derive a score ranging from 0 (low quality) to 5 (high quality).…”
Section: Assessment Of Study Qualitymentioning
confidence: 99%
“…[2] Many natural substances have been identified in green tea; [4] the theanine and catechins components have neuroprotective functions, [5,6] and the catechins inhibit tumor cell proliferation and promote destruction of leukemia cells [7,8] and breast cancer cells. [9] Studies have shown that green tea decreases the risk of ovarian cancer [10] and reduces the proliferation of cervical, [11] prostate [12] and pancreatic carcinoma cells. [13] Green tea was shown to be an aromatase inhibitor in rat; [14] a causative factor for an increase in testosterone level.…”
Section: Introductionmentioning
confidence: 99%